LEGAL PROTECTION FOR VICTIMS OF DOMESTIC VIOLENCE REVIEWED FROM THE LEGAL SYSTEM IN INDONESIA - Beatrix, Marisca Lian; Irawan, Haris; Ohoiledyaan, Januarius Rizky (Jurnal Hukum Khaira Ummah, 2024)
Domestic violence is a problem within the household that is private and taboo if brought to the public. Domestic violence is generally experienced by women by men or their husbands. Domestic violence is a problem that cannot be resolved by the Criminal Code, so it is regulated in more depth in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. There are several factors that trigger domestic violence. The forms of violence experienced by victims are generally in addition to physical violence, also verbal violence and sexual violence. Many settlements of domestic violence cases do not fulfill a sense of justice, especially for victims whose rights are not fulfilled. Law enforcement in the implementation of protection for victims of domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence is urgently needed. This research is juridical-normative, which means that several legal sources such as legislation and also the opinions of several legal experts regarding cases of domestic violence that occur in Indonesia are reviewed, this aims to find out how the legal protection process is given to victims of domestic violence.